The practice and exploration of SPOC-based online-offline mixed teaching mode in Traditional Chinese Medicine nursing teaching (基于SPOC的线上-线下混合式教学模式在中医护理教学中的实践与探索) - WANG Li (王黎); MA Xueling (马雪玲); WANG Zhen (王臻); CHEN Hong (陈宏); WENG Zhiwen (翁志文); WANG Junxiang (王俊翔) (Association of Integrative Nursing, 2022)
Objective To evaluate the implementation effects of Small Private Online Course(SPOC)-based online-offline mixed teaching mode in Traditional Chinese Medicine nursing teaching. Methods Totally 593 students from Grade 2019 and Grade 2020 of the School of Nursing of Beijing University of Chinese Medicine were taught with online-offline mixed teaching mode, the scores of whom were then compared with the scores of 371 students from Grade 2017 and Grade 2018 of the school of Nursing. In addition, interview was conducted to several students who were taught with online-offline mixed teaching mode, which means the effects of online-offline mixed teaching mode were evaluated from both subjective and objective perspectives. Results Before and after the implementation of the online-offline mixed teaching mode, there were significant differences in students' total scores (P<0. 01), formative assessment scores (P<0. 05) and operational assessment scores (P<0. 01), while there were no significant differences in summative assessment scores, daily homework scores and experimental report scores (P>0. 05). Students believed that the online-offline mixed teaching model effectively promoted their independent learning capability, but lacked effective interaction between teachers and students. Conclusion SPOC-based online-offline mixed teaching model can effectively improve students' subjective initiative in learning and more objectively reflect the effects of students' process learning. However, there are still some problems in the implementation of this teaching model, such as teachers and students being unable to communicate in time and relying too much on students' autonomy, which need to be further improved. (目的 评价基于SPOC的线上-线下混合式教学模式的实施效果。方法 对北京中医药大学护理学院2019级和2020级二本层次593名学生实施线上-线下混合式教学, 将学生成绩与教学改革实施前的2017级和2018级二本层次371名学生的成绩进行比较分析, 并对教学改革实施后的部分学生进行访谈, 从主客观两个角度评价线上-线下混合式教学模式的效果。结果 线上-线下混合式教学模式实施前后, 学生总成绩(P＜0. 01)、形成性考核成绩(P＜0. 05)及操作考核成绩(P＜0. 01)差异有统计学意义, 终末考核成绩、平时作业成绩及实验报告成绩均无显著差异(P＞0. 05)。学生认为, 线上-线下混合式教学模式有效推动了他们自主学习, 但缺乏师生有效互动。结论 基于SPOC的线上-线下混合式教学模式, 能够有效提升学生学习的主观能动性, 并能够更加客观地反映学生的过程性学习效果, 但教学模式实施过程中仍存在师生无法及时沟通、过于依赖学生自主性等问题, 有待进一步改善。)